Community radio stations sustainability model: An open-source solution. (1st April 2019) - Correia, Rute; Vieira, Jorge; Aparicio, Manuela
Community radio stations are important social-inclusion structures, empowering communities through media access and production, reinforcing their ties with the wider civil society. The free and open-source software movement has been established since the 1980s, founded on the freedom to use, to study, to share and to improve a software's source code. It focuses on sharing knowledge, enabling action within a community towards a common goal. With millions of projects and market dominance in specific areas of IT, open source is one of the most successful community movements of our time. In this article, we argue that theoretical frameworks and other insights drawn from the open-source movement can be valuable tools for understanding and critically analysing the designated community radio sphere in terms of technology, content creation and community management to provide a sustainable broadcast practice, expanding already-existing inclusive environments and potentiating empowerment through participation.